Pengetahuan Penduduk terhadap Peta Kawasan Rawan Bencana dan Mitigasi Bencana Merapi - Laksmi Rachmawati (Jurnal Kependudukan Indonesia, 2018)
The risk of volcanic disasters is increasing over time due to population growth and the increase of settlements around volcanoes. In addition, the centres of economic growth and infrastructure development around this area also further increase the vulnerability of the population living around of the volcano.Â  The choice to live around volcanoes should be followed by knowledge on hazard, hazard zone and the alert status of a volcano as part of the early warning system platform. However, in reality, the understanding of hazard-prone areas and hazard maps is still limited. This paper aims to examine the knowledge of people living around of Merapi on Hazard map (peta Kawasan Rawan Bencana â€“ KRB) and the understanding of hazard-prone areas in Merapi related to mitigation efforts. In addition, to communicate risk by paying attention to the Living in harmony with environment approach are also examined, to provide a complete understanding of the knowledge of hazard map and early warning systems. Data collection was conducted in 2012 and 2014 by using qualitative approach (interviews, focus group discussions and observations) and using quantitative approach (survey of 600 respondents which distributed evenly in the KRB III-I and outside of KRB areas). The findings of the research at Merapi showed that 54 per cent of respondents know about disaster-prone areas. In addition, from respondents who knew about disaster-prone areas, only 49 per cent had seen maps of hazard map (KRB). Changes to the KRB map due to changes in the naming of zoning and 2010 eruption events are indicated to be a factor in the limitations of understanding disaster-prone areas. In addition, information dissemination and public perceptions of areas considered safe are also other factors discussed in this paper. Therefore a more effective risk communication strategy, which integrates spatial early warning (KRB map), Merapi alert status and traditional acceptance of early warning becomes a necessity for Merapi disaster mitigation.